Ostium Ratio and Neck Ratio Could Predict the Outcome of Sidewall Intracranial Aneurysms Treated with Flow Diverters - Paliwal, N.; Tutino, V.M.; Shallwani, H.; Beecher, J.S.; Damiano, R.J.; Shakir, H.J.; Atwal, G.S.; Fennell, V.S.; Natarajan, S.K.; Levy, E.I.; Siddiqui, A.H.; Davies, J.M.; et al. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Incompletely occluded flow diverter treated aneurysms remain at risk of rupture and thromboembolic complications. Our aim was to identify the potential for incomplete occlusion of intracranial aneurysms treated by flow diverters. We investigated whether aneurysm ostium size in relation to parent artery size affects angiographic outcomes of flow diverter–treated sidewall aneurysms.MATERIALS AND METHODS: Flow diverter–treated sidewall aneurysms were divided into “occluded” and “residual” (incomplete occlusion) groups based on 6-month angiographic follow-up. We calculated the ostium ratio, a new parameter defined as the aneurysm ostium surface area versus the circumferential surface area of the parent artery. We also calculated the neck ratio, defined as clinical aneurysm neck diameter versus parent artery diameter from pretreatment 2D DSA, as a 2D surrogate. We compared the performance of these ratios with existing aneurysm morphometrics (size, neck diameter, volume, aspect ratio, size ratio, undulation index, nonsphericity index, ellipticity index, bottleneck factor, aneurysm angle, and parent vessel angle) and flow diverter–related parameters (metal coverage rate and pore density). Statistical tests and receiver operating characteristic analyses were performed to identify significantly different parameters between the 2 groups and test their predictive performances.RESULTS: We included 63 flow diverter–treated aneurysms, 46 occluded and 17 residual. The ostium ratio and neck ratio were significantly higher in the residual group than in the occluded group (P < .001 and P = .02, respectively), whereas all other parameters showed no statistical difference. As discriminating parameters for occlusion, ostium ratio and neck ratio achieved areas under the curve of 0.912 (95% CI, 0.838–0.985) and 0.707 (95% CI, 0.558–0.856), respectively.CONCLUSIONS: High ostium ratios and neck ratios could predict incomplete occlusion of flow diverter–treated sidewall aneurysms. Neck ratio can be easily calculated by interventionists to predict flow-diverter treatment outcomes.CNDclinical neck diameterFDflow diverterMCRmetal coverage rateNRneck ratioOsRostium ratioVSWvirtual stenting workflow